Implementation of a prostate cancer‐specific targeted sequencing panel for credentialing of patient‐derived cell lines and genomic characterization of patient samples. Issue 5 (27th January 2022) - Stover, Elizabeth H.; Oh, Coyin; Keskula, Paula; Choudhury, Atish D.; Tseng, Yuen‐Yi; Adalsteinsson, Viktor A.; Lohr, Jens G.; Thorner, Aaron R.; Ducar, Matthew; Kryukov, Gregory V.; Ha, Gavin; Rosenberg, Mara; et al.
Abstract: Background: Primary and metastatic prostate cancers have low mutation rates and recurrent alterations in a small set of genes, enabling targeted sequencing of prostate cancer‐associated genes as an efficient approach to characterizing patient samples (compared to whole‐exome and whole‐genome sequencing). For example, targeted sequencing provides a flexible, rapid, and cost‐effective method for genomic assessment of patient‐derived cell lines to evaluate fidelity to initial patient tumor samples. Methods: We developed a prostate cancer‐specific targeted next‐generation sequencing (NGS) panel to detect alterations in 62 prostate cancer‐associated genes as well as recurring gene fusions with ETS family members, representing the majority of common alterations in prostate cancer. We tested this panel on primary prostate cancer tissues and blood biopsies from patients with metastatic prostate cancer. We generated patient‐derived cell lines from primary prostate cancers using conditional reprogramming methods and applied targeted sequencing to evaluate the fidelity of these cell lines to the original patient tumors. Results: The prostate cancer‐specific panel identified biologically and clinically relevant alterations, including point mutations in driver oncogenes and ETS family fusion genes, in tumor tissues from 29 radical prostatectomy samples. The targeted panel also identified genomic alterations in cell‐free DNA and circulating tumor cells (CTCs) from patients with metastatic prostate cancer, and in standard prostate cancer cell lines. We used the targeted panel to sequence our set of patient‐derived cell lines; however, no prostate cancer‐specific mutations were identified in the tumor‐derived cell lines, suggesting preferential outgrowth of normal prostate epithelial cells. Conclusions: We evaluated a prostate cancer‐specific targeted NGS panel to detect common and clinically relevant alterations (including ETS family gene fusions) in prostate cancer. The panel detected driver mutations in a diverse set of clinical samples of prostate cancer, including fresh‐frozen tumors, cell‐free DNA, CTCs, and cell lines. Targeted sequencing of patient‐derived cell lines highlights the challenge of deriving cell lines from primary prostate cancers and the importance of genomic characterization to credential candidate cell lines. Our study supports that a prostate cancer‐specific targeted sequencing panel provides an efficient, clinically feasible approach to identify genetic alterations across a spectrum of prostate cancer samples and cell lines.